Assessing the efficacy of oral immunotherapy for the desensitisation of peanut allergy in children (STOP II): a phase 2 randomised controlled trial: a critical appraisal. (November 2015) - Marrs, T.; Flohr, C.; Perkin, M.R.
Summary: Aim: Anagnostou et al . investigated the efficacy of oral immunotherapy (OIT) in treating peanut allergy. Setting and design: An unmasked randomized controlled crossover trial of 7–16 year olds with double‐blind placebo‐controlled food challenge (DBPCFC)‐proven peanut allergy. The first phase compared an active group undergoing 26 weeks of OIT with daily ingestion of peanut protein vs. a control group avoiding peanuts. Both groups underwent DBPCFC to peanut at 26 weeks. In the second phase the control group was then offered OIT for 26 weeks. Study exposure: Participants undergoing OIT attended hospital every 2 weeks to initiate and increase their daily peanut protein dose through nine stages (2, 5, 12·5, 25, 50, 100, 200, 400 and 800 mg – about five peanuts), subsequently maintaining consumption at the highest tolerated dose. Primary outcome The primary outcome compared the proportions of active‐ and control‐group participants able to ingest a cumulative dose of 1400 mg of peanut protein (about 10 peanuts) during their DBPCFC at the end of the first phase without reacting. Secondary outcomes Further outcomes included the proportion of participants who tolerated the top maintenance dosage of 800 mg protein up to 26 weeks; the proportion of the control group who were desensitized or tolerated daily ingestion of 800 mg protein in the second phase; threshold changes in no observed adverse effect level after OIT (NOAEL: defined as the highest dose of peanut protein tolerated in milligrams of protein during challenge or immunotherapy); change in quality of life; number and type of adverse events; and immunological parameters (basophil reactivity, peanut‐specific IgE, total IgE and skin‐prick test). Results: Primary outcome Twenty‐four of 39 (62%) of the active group were able to tolerate the 1400 mg of peanut protein during their DBPCFC after 26 weeks of OIT, compared with none of the 46 control participants ( P < 0·001). Secondary outcomes Twenty‐five of 46 (54%) of the control group had a negative 1400‐mg peanut protein challenge at the end of phase 2. Combining the two groups, 49 of 85 children (58%) were desensitized. Thirty‐three of 39 (85%) active participants in phase one and 42 of 46 (91%) control participants in phase two tolerated 800 mg of OIT daily – a combined result of 75 of 85 (88%) trial participants. The median absolute change in NOAEL between baseline and 26 weeks was 1345 mg ( P = 0·002), or a 25·5‐fold increase ( P < 0·001) for the active group. Both the active and control groups demonstrated a significant improvement (decrease) in Food Allergy Quality of Life scores after OIT in the under‐13‐year‐old participants: −1·61 and −1·41, respectively (both P < 0·001). Mild side‐effects predominated, with 54 (57%) reporting abdominal pain and 31 (33%) reporting vomiting. However, 21 (22%) also reported wheezing and one (1%) laryngeal oedema. One participant received adrenaline by self‐administration on two occasions for wheezing. Conclusions: Anagnostou et al . concluded that OIT successfully induced desensitization in challenge‐proven peanut‐allergic children and resulted in a clinically and socially meaningful increase in tolerated peanut protein. Quality of life improved after intervention and there was a good safety profile.